2009
DOI: 10.1038/ijo.2009.21
|View full text |Cite
|
Sign up to set email alerts
|

Effects of strategies to promote children's physical activity on potential mediators

Abstract: The aim of this paper is to review evidence of the effectiveness of interventions that present physical activity outcomes and potential mediators of behavioural change among 4-12-year-old children. A systematic search of electronic databases for original research articles published in peer-review journals between January 1985 and the end of June 2006 was carried out. A total of 19 studies that reported intervention effects on physical activity and mediators of behavioural change were identified. The most commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 27 publications
5
66
2
Order By: Relevance
“…Self-efficacy has been demonstrated as a consistent correlate and mediator of adolescents' physical activity [10,11,14,16,43,44]. However, in the current study, selfefficacy did not directly affect physical activity of adolescent girls.…”
Section: Discussioncontrasting
confidence: 77%
“…Self-efficacy has been demonstrated as a consistent correlate and mediator of adolescents' physical activity [10,11,14,16,43,44]. However, in the current study, selfefficacy did not directly affect physical activity of adolescent girls.…”
Section: Discussioncontrasting
confidence: 77%
“…Additionally, as enjoyment has been identified as a possible mediator for PA (Salmon et al, 2009), the impact of PLUNGE in influencing enjoyment during PE classes was included. PLUNGE was evaluated using a group randomized control trial (RCT) with a 7-week wait-list control group.…”
Section: Introductionmentioning
confidence: 99%
“…9 She also emphasized the importance of considering studies documenting interventions that present physical activity outcomes and that report on effects on potential mediators of behavior change in children. The meta-analysis that she performed with her colleagues revealed that the most common mediators reported included physical activity knowledge or beliefs, self-efficacy, and enjoyment or preference for physical activity.…”
Section: Effects Of Strategies To Promote Physical Activitymentioning
confidence: 99%
“…9 Hopefully, this could also help us understand why other activities, for example computer-related activities, promote a more spontaneous adherence than physical activity.…”
Section: Effects Of Strategies To Promote Physical Activitymentioning
confidence: 99%